Assessing the need for home-based end-of-life palliative care in pediatric cancer care - Anukriti Srivastava; Nita Radhakrishnan; Archit Pandharipande; Shruti Verma; Zeenat Brar; Eby P Baby (Asian Journal of Medical Sciences, 2024)
Background: Palliative care is underrepresented in our community at large. End-of-life care is offered mainly in palliative care hospices or hospitals worldwide. As access to such a facility is often sparse, and since many of them are located far away from home, most families wish to go home if a curative treatment option does not exist. Aims and Objectives: The study was done to analyze the preferences for the location of end-of-life care for families of children with cancer. We analyze the reasons for the same and offer suggestions for improving this situation. Materials and Methods: Parents of 77 children who died following a diagnosis of childhood cancer between 2019 and 2023, either due to progressive or refractory disease or due to toxic death, were interviewed to understand their choice of location for end-of-life care. The interview was done telephonically or face to face. Results: 41 out of 77 deaths were anticipated, and out of these, we observed that only 3 (7.3%) opted for a formal palliative care center. Fifteen families (36%) opted for end-of-life treatment in the hospital, and 23 families (56%) went home despite having no support at home for palliation. The decision is taken considering the practical needs of the rest of the family, although it is more difficult to implement. The reasons behind the decision are analyzed here. Conclusion: We recommend that integrated home-based palliation for end-of-life care in children be developed instead of hospice support. Hospices that take care of adults may be used with children where required. A multidisciplinary team that can support the needs of families and can visit them at home needs to be developed around centers managing children with cancer.